Statistical shape analysis using landmark for craniofacial classification - Md. Hussin, Mohd. Bakery; Setan, Halim; Majid, Zulkepli; Suwardhi, Deni (2006)
This paper describes craniofacial medical application, with the emphasis on the craniofacial classification by using statistical shape analysis method to classify the craniofacial datasets. The craniofacial datasets are classified by gender of the datasets. Craniofacial classification involves the construction and description of the craniofacial dataset classes, and then craniofacial classification involves assigning the craniofacial dataset into the known classes. The data consists of 3D laser scans of normal human faces with respect to the normal craniofacial dataset. Craniofacial datasets using 8 landmarks with 3D coordinate on the facial surface. The craniofacial landmarks coordinate are used to analyze the datasets, and classify the datasets into the classes that has created.